The Effect of Tebuh Sari Drinking After Training on Hydration Status and Blood Glucose Levels of Football Athletes PSDKU Aru - Wilhelmina Unmehopa (Peneliti.net, 2022)
The purpose of this study was to determine the effect of giving sugarcane juice after exercise on hydration status and blood glucose levels of PSDKU Aru soccer athletes. This type of research is an experimental research Pre-Experimental Design, namely one group pretest-posttest design. In this design, the testee will be given a test before being given treatment. The results showed that 1) the administration of sugarcane juice after it could restore blood glucose levels. 2) Giving sugarcane juice is better to maintain hydration status.